Compartmental distribution of GABAB receptor-mediated currents along the somatodendritic axis of hippocampal principal cells - Degro, Claudius E.; Kulik, Akos; Booker, Sam A.; Vida, Imre (Frontiers in Synaptic Neuroscience, 2015)
Activity of cortical principal cells is controlled by the GABAergic system providing inhibition in a compartmentalized manner along their somatodendritic axis. While GABAAR-mediated inhibitory synaptic transmission has been extensively characterized in hippocampal principal cells, little is known about the distribution of postsynaptic effects of GABABRs. In the present study, we have investigated the functional localization of GABABRs and their effector inwardly rectifying potassium (Kir3) channels by combining electrophysiological recordings in acute rat hippocampal slices, high-resolution immunoelectron microscopic analysis and single cell simulations. Pharmacologically-isolated slow inhibitory postsynaptic currents were elicited in the three major hippocampal principal cell types by endogenous GABA released by electrical stimulation, photolysis of caged-GABA, as well as the canonical agonist baclofen, with the highest amplitudes observed in the CA3. Spatially restricted currents were assessed along the axis of principal cells by uncaging GABA in the different hippocampal layers. GABABR-mediated currents were present along the entire somatodendritic axis of principal cells, but non-uniformly distributed: largest currents and the highest conductance densities determined in the simulations were consistently found on the distal apical dendrites. Finally, immunocytochemical localization of GABABRs and Kir3 channels showed that distributions overlap but their densities diverge, particularly on the basal dendrites of pyramidal cells. GABABRs current amplitudes and the conductance densities correlated better with Kir3 density, suggesting a bottlenecking effect defined by the effector channel. These data demonstrate a compartmentalized distribution of the GABABR-Kir3 signaling cascade and suggest differential control of synaptic transmission, dendritic integration and synaptic plasticity at afferent pathways onto hippocampal principal cells.